FARMER-HERDERS CONFLICTS IN NIGERIA: ITS CHALLENGES AND INTERVENTIONS - M.O. Mazeli; Binta Side (International Studies Journal)
Climate change has forced herders to move out of the desert to the forest, searching for a greener posture but not ethnic war. How the address these challenges remains a challenge for this regime and even the next regime. The chapter reveals the role of President Buhari's administration in curbing the farmer-herders conflict. All the attempts at conceptualizing lasting solutions to the crisis faced politicization. This chapter urges states to join the federal government at the center in encouraging all sides to these conflicts to make efforts towards finding a peaceful resolution. As we seek a permanent solution to these unwanted conflicts, efforts must be made to ensure that no innocent person faces any kind of deprivation or loss of rights and freedom under our laws. The fight for peace in the north-central states, the fight against social insecurity and conflicts, must comprise determined action against food security, poverty, inequality, injustice, and against the most extreme and most dependence-inducing form of poverty - being hungry, insecure of today's and tomorrow's food. Access to land is a major cause of conflicts in this region. Central to the discussion in this paper is the need for the State to review the existing laws as they relate to accessibility to land by members of the community. This issue is key to resource sustainability in Nigeria as the majority of its citizens require land for farming and grazing. The government should ensure that there is equity and accessibility to arable and grazing land to avert constant conflict.